2006
DOI: 10.1002/ajh.20813
|View full text |Cite
|
Sign up to set email alerts
|

Superior effect of intravenous anti‐D compared with IV gammaglobulin in the treatment of HIV‐thrombocytopenia: Results of a small, randomized prospective comparison

Abstract: This small, prospective, randomized study compared increases in platelet counts and duration of response after intravenous gammaglobulin (IVIG) and IV anti-D in patients with HIVrelated thrombocytopenia (HIV-TP). Nine Rh+, nonsplenectomized HIV-positive patients with thrombocytopenia were treated sequentially, in random order, with IVIG and IV anti-D in a cross over design, receiving each therapy for 3 months. Peak platelet counts and duration of effect after each treatment were compared. In addition, viral lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…This is consistent with findings from the study by Landonio, in which only four of 17 patients treated with IVIG had sustained remissions, and all patients treated with steroids had recurrent ITP after discontinuation of initial therapy [8]. In a randomized cross-over study of nine patients with severe HIV-associated ITP, Scaradavou found the median duration of response was 19 days following treatment with IVIG and 41 days following anti-RhD [17]. …”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with findings from the study by Landonio, in which only four of 17 patients treated with IVIG had sustained remissions, and all patients treated with steroids had recurrent ITP after discontinuation of initial therapy [8]. In a randomized cross-over study of nine patients with severe HIV-associated ITP, Scaradavou found the median duration of response was 19 days following treatment with IVIG and 41 days following anti-RhD [17]. …”
Section: Discussionsupporting
confidence: 88%
“…No changes in CD4 counts or viral loads were reported. 25 Although there was a small number of patients in this study, this confirms previous results. 20,26 …”
Section: Anti-d In Secondary Immune Thrombocytopeniasupporting
confidence: 93%
“…Most patients treated with WinRho for ITP or secondary thrombocytopenia do not experience signs/symptoms of acute hemolysis, 1,3‐13 and not all who experience signs/symptoms of acute hemolysis experience hemolysis‐related complications 14 or require medical intervention for any complications experienced 13‐16 . Nonetheless, the acute hemolysis–associated complications that have been reported to date include clinically significant anemia, the need for RBC transfusion(s), acute or exacerbated renal failure, the need for dialysis, disseminated intravascular coagulation, and death secondary to these complications 14,17 .…”
mentioning
confidence: 99%